2012 Benjamin Franklin Medal in Computer and Cognitive Science presented to Vladimir Vapnik. Issue 7 (July 2015) - Jose Taylor, Camillo
Abstract The Franklin Institute, Philadelphia, Pennsylvania, awards the 2012 Benjamin Franklin Medal in Computer and Cognitive Science to Professor Vladimir Vapnik for his fundamental contributions to our understanding of machine learning, which allows computers to classify new data based on statistical models derived from earlier examples, and for his invention of widely used machine learning techniques.